CONTENT ANALYSIS OF 11TH GRADE ENGLISH TEXTBOOK (2017 REVISE EDITION) PUBLISHED BY KEMENTERIAN PENDIDIKAN DAN KEBUDAYAAN REPUBLIK INDONESIA - Dian Septiana Manurung; Lince Lestari; Christin Natalia Hutagalung; Epiana Banjarnahor; Erikson Saragih (JURNAL HANDAYANI PGSD FIP UNIMED, 2019)
Abstract: This research was purposed to analyze the content of 11th grade English textbook (2017 revise edition) published by Kementerian Pendidikan dan Kebudayaan Republik Indonesia. This study used descriptive qualitative research design. The data source is 11th grade English textbook (2017 revise edition) published by Kementerian Pendidikan dan Kebudayaan Republik Indonesia. This study used content analysis as the method by using four evaluation’s instruments formulated by BSNP, namely content, presentation, language and graphic. The total of average percentage got 94% which categorized as good. Keywords: Content analysis, English textbook, evaluation. Abstrak: Penelitian ini bertujuan untuk menganalisis isi buku teks bahasa Inggris kelas 11 (edisi revisi 2017) yang diterbitkan oleh Kementerian Pendidikan dan Kebudayaan Republik Indonesia. Penelitian ini menggunakan desain penelitian deskriptif kualitatif. Sumber data adalah buku teks bahasa Inggris kelas 11 (edisi revisi 2017) yang diterbitkan oleh Kementerian Pendidikan dan Kebudayaan Republik Indonesia. Penelitian ini menggunakan analisis isi sebagai metode dengan menggunakan empat instrument evaluasi yang dirumuskan oleh BSNP, yaitu konten, presentasi, bahasa dan grafik. Total persentase rata-rata mendapat 94% yang dikategorikan baik. Kata kunci: Analisis konten, buku teks bahasa Inggris, evaluasi.